Complications during hemodialysis in arterio-venous fistula versus temporary vascular access (Iraqi Journal of Medical Sciences, 2009)
Background: Dialysis is procedure that removes excess fluid and the toxic end products of metabolism. The major forms of dialysis are hemodialysis, and peritoneal dialysis. Access to the blood circulation is achieved by the use of central venous catheter or artificial arteriovenous fistula.Objective: To detect and compare prevalence of complications occurs in uremic patients using central venous catheter or arteriovenous fistula in dialysis unit in Al-Kadhimiya Teaching Hospital.Patients and methods: One hundred patients with renal failure (chronic or acute) undergoing hemodialysis were questioned and examined for theComplications occurred during or after the hemodialysis process using arteriovenous fistula or temporary vascular access.Results: The results showed significant of fever and blood flow obstruction in temporary vascular access (